2018
DOI: 10.1107/s2053230x18009093
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human anterior gradient protein 3

Abstract: Oxidative protein folding in the endoplasmic reticulum is catalyzed by the protein disulfide isomerase family of proteins. Of the 20 recognized human family members, the structures of eight have been deposited in the PDB along with domains from six more. Three members of this family, ERp18, anterior gradient protein 2 (AGR2) and anterior gradient protein 3 (AGR3), are single-domain proteins which share sequence similarity. While ERp18 has a canonical active-site motif and is involved in native disulfide-bond f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Compromised mucociliary clearance contributes to changes in relative proportions and viscosity of host mucins, which, in turn, contribute to airway obstruction [ 68 ]. AGR3 was shown to interact with mucins [ 69 ] and this may explain its binding to Tc-MUC-3, which is a mucin-like glycoprotein [ 13 ]. It remains to be confirmed if, and to what extent, this interaction may contribute to the pathology of toxocariasis.…”
Section: Discussionmentioning
confidence: 99%
“…Compromised mucociliary clearance contributes to changes in relative proportions and viscosity of host mucins, which, in turn, contribute to airway obstruction [ 68 ]. AGR3 was shown to interact with mucins [ 69 ] and this may explain its binding to Tc-MUC-3, which is a mucin-like glycoprotein [ 13 ]. It remains to be confirmed if, and to what extent, this interaction may contribute to the pathology of toxocariasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in airway epithelium where it is required for muco-ciliary clearance and for regulation of ciliary beat frequency (32). It is also expressed in prostate, as well as stomach and liver tissues of the digestive tract (33).…”
Section: Genes Structures and Regulatorsmentioning
confidence: 99%
“…AGR2 and AGR3 expression are coupled in EsR positive breast cancer and the combination of AGR2 and AGR3 as biomarkers resulted in increased sensitivity and specificity thus suggesting that they can be used as a prognostic factor [ 113 ]. The crystal structure of AGR3 (PDB code:3PH9) has revealed that it can form an asymmetric unit consisting of two AGR3 molecules, however, there was no evidence that AGR3 can form a spontaneous dimer in solution [ 114 ].…”
Section: Functions and Mechanisms Of Pdi Members In Cancermentioning
confidence: 99%